1972
DOI: 10.1111/j.1365-2133.1972.tb07418.x
|View full text |Cite
|
Sign up to set email alerts
|

Pilo-Sebaceous Duct Obstruction and Acne

Abstract: Summary.— The outermost part of the epidermis, including part of the pilo‐sebaceous apparatus, has been sampled, using a cyanoacryalnte adhesive, in patients with acne of varying severity, controls, and in acne patients treated with long term tetracycline. At the site sampled (left upper hack) patients with acne have an increased amount of inspissated material as compared with controls; this appears increased in relation to the severity of the acne. The inspissated material, which is partly keratin and partly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
2
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 14 publications
3
39
2
4
Order By: Relevance
“…The further studies of Plewig et al [18]and Holmes et al [19]showed that even normal-looking skin from acne patients may already be developing very early microcomedones; this was further supported by the work of Cunliffe et al [20]using in situ hybridisation techniques. This observation is of clinical significance since it stresses the need to apply topical therapies, not just to acne lesions but also to the normal-looking skin of the acne-prone areas.…”
Section: Comedone Formationsupporting
confidence: 52%
“…The further studies of Plewig et al [18]and Holmes et al [19]showed that even normal-looking skin from acne patients may already be developing very early microcomedones; this was further supported by the work of Cunliffe et al [20]using in situ hybridisation techniques. This observation is of clinical significance since it stresses the need to apply topical therapies, not just to acne lesions but also to the normal-looking skin of the acne-prone areas.…”
Section: Comedone Formationsupporting
confidence: 52%
“…Such evaluations were made on CFB taken from symmetrical sites of the forehead at the baseline visit as well as after 2, 4 and 6 weeks of treatment. CFB was developed as an extension of skin surface stripping and refers to a non-invasive collection of stratum corneum and follicular material using cyanoacrylate adhesive [16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26]. The follicular casts so sampled from the upper portion of a follicular duct reflect the balance between comedo formation and lysis.…”
Section: Methodsmentioning
confidence: 99%
“…Comedogenesis is due to the accumulation of corneocytes in the pilosebaceous duct [5]. This could be due to hyperproliferation of ductal keratinocytes, inadequate separation of the ductal corneocytes or a combination of both factors [6].…”
Section: Aetiology Of Comedogenesismentioning
confidence: 99%